Digital literacy outreach: Wise use of digital media in Sumberjaya Village, Sumur, Pandeglang - Ula, Shofiatul; Susilo, Sidik; Pinem, Mekro Permana; Abdullah, Syarif; Pramujad, Adam; Zaidan, Athallah (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
The advancement of digital technology has reached various regions in Indonesia, including Sumberjaya Village, where internet access—particularly through smartphones—is widely available. While digital media offers numerous benefits, it also presents potential risks. Therefore, understanding appropriate usage guidelines, communication ethics, and information filtering is essential to minimize negative impacts. This community outreach program employed a participatory group method consisting of four main stages: observation, presentation, focus group discussion (FGD), and evaluation. The results of the program indicate that participants have significantly improved their digital literacy across three core dimensions: technological proficiency, cognitive awareness, and ethical behavior. These enhancements are expected to contribute positively to the community’s overall quality of life and resilience in navigating digital environments. Kemajuan teknologi digital telah merambah berbagai daerah di Indonesia, termasuk Desa Sumberjaya, yang akses internetnya sudah sangat luas, khususnya melalui telepon pintar. Media digital menawarkan banyak manfaat, tetapi juga berpotensi menimbulkan risiko. Oleh karena itu, pemahaman tentang pedoman penggunaan, etika komunikasi, dan penyaringan informasi yang tepat sangat penting untuk meminimalkan dampak negatif. Program pengabdian masyarakat ini menggunakan metode kelompok partisipatif yang terdiri dari empat tahap utama: observasi, presentasi, diskusi kelompok terfokus (FGD), dan evaluasi. Hasil program menunjukkan bahwa peserta telah meningkatkan literasi digital secara signifikan dalam tiga dimensi inti: kemahiran teknologi, kesadaran kognitif, dan perilaku etis. Peningkatan ini diharapkan dapat memberikan kontribusi positif terhadap kualitas hidup masyarakat secara keseluruhan dan ketahanan dalam mengarungi lingkungan digital.